Blood parameters in neonatal foal and colostrum quality as possible early markers for increased risk of developing Rhodococcus equi pneumonia - Villalba-Orero, María; Gómez, Camila A.; Valero-Gónzalez, Marta; Venegas, Noelia; Criado, Guadalupe; Martín-Cuervo, María (Frontiers in Veterinary Science, 2025)
BackgroundRhodococcus equi is a facultative intracellular bacterium recognized to cause pneumonia in foals aged 1 to 6 months. Currently, it remains a challenge to identify foals at risk.Hypothesis/ObjectivesWe hypothesize that a certain grade of immaturity may enhance the risk for future R. equi infection. This study aims to analyze blood parameters and passive immunity transfer within the first 24 hours of life as predictive markers for the development of R. equi pneumonia during the first 6 months of life.MethodsA total of 207 Arabian or Arabian-crossed breed foals from the same breeding center, from birth to 6 months of age, were included. Blood samples were obtained from foals during the first 24 hours after birth. Parameters analyzed were hematocrit (Hto), total white blood cell count (WBC), total plasma proteins (PT), albumin (ALB), fibrinogen (FBG), urea (U), creatinine (CREA), gamma-glutamyl transferase (GGT), iron (Fe), and serum immunoglobulin G (IgG). In addition, colostrum Brix was measured. Foals were classified into the following groups: foals presenting R. equi (R group) and healthy foals (H group), which showed no signs of pneumonia during a surveillance period of six months.ResultsComparisons were performed between the two groups, and univariable and multivariable logistic regression were used to assess possible predictors for R. equi development. Of the 207 foals, 25 became ill (12.08 %). Foals with R. equi showed lower U levels [H: 29 (23-37) Vs R: 24 (20-31); p = 0.04], as higher CREA [H: 1.3 (1.1-1.6) Vs R: 1.5 (1.3-1.7); p = 0.03], and GGT [H: 14 (10-24) Vs R: 21 (12-39); p = 0.004] than foals with a healthy status. Multivariable logistic regression highlighted that higher GGT at birth was associated with R. equi development.DiscussionHigh values of GGT and CREA have been associated with fetal immaturity, which could be related to immaturity of the immune system, especially of alveolar macrophages, and may predispose to early infection by R. equi. Interestingly, neonatal GGT may serve as a possible risk factor for developing the infection.